PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS KONSTRUKTIVISME DENGAN MULTIMEDIA INTERAKTIF UNTUK MENGAJARKAN KONSEP MATEMATIKA - Caka Gatot Priambodo; Aulia Ar Rakhman Awaludin; Nur Alamsyah (AKSIOMA : Jurnal Matematika dan Pendidikan Matematika, 2017)
This research aims to develop and produce constructivism based learning device using interactive multimedia to teach the valid mathematics concepts of SMP (feasible) and to know the effectiveness of constructivism based learning devices using interactive multimedia to teach math concepts. The sampling technique in this product testing experiment used simple random sampling because the sampling of sample members from the population is done randomly without considering the strata in the population. The result of research is process and result of development of learning device based on cosntruktivisme with interactive multimedia to teach mathematics concept of junior high school students valid. Mathematical learning based on constructivism using interactive multimedia to teach the concept of SMP mathematics is more effective than conventional learning on the matter of building flat side space.Keywords: Development of learning tools, constructivism, interactive multimedia, Concepts.